1978
DOI: 10.1007/bf00484381
|View full text |Cite
|
Sign up to set email alerts
|

Control of drosopterin synthesis in Drosophila melanogaster: Mutants showing an altered pattern of GTP cyclohydrolase activity during development

Abstract: The reaction catalyzed by GTP cyclohydrolase is the first unique step of pteridine biosynthesis in Drosophila melanogaster and is therefore likely to be an important control point. GTP cyclohydrolase activity varies during development, showing two distinct peaks of activity--one at pupariation and a much larger peak at emergence. Most of the early pupal enzyme is located in the body region, whereas in late pupal and early adult life most of the activity is found in the head. Mixing experiments indicate that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Consistent with the expression profile of GTPCH I, Drosophila exhibits a characteristic activity profile of GTPCH I during the life cycle (25, 26). Two peaks of GTPCH I activity occur during development.…”
Section: Enzymesmentioning
confidence: 60%
“…Consistent with the expression profile of GTPCH I, Drosophila exhibits a characteristic activity profile of GTPCH I during the life cycle (25, 26). Two peaks of GTPCH I activity occur during development.…”
Section: Enzymesmentioning
confidence: 60%
“…The first and rate-limiting step in pteridine synthesis is catalyzed by the enzyme GTP cyclohydrolase (GTPCH), which converts substrate GTP to dihydroneopterine triphosphate (39). It has been shown that in pn mutants the pteridine level is reduced and the activity levels of GTPCH becomes variable (40). Since Nm23/Awd as a NDPK is presumed to supply nucleoside triphosphate, thus driving the forward reaction catalyzed by GTPCH, the defects in pn mutants are consistent with the genetic data that implicate Pn as an antagonist of Nm23/Awd.…”
Section: The Function Of Pnmentioning
confidence: 99%
“…hs-FLP and w1118 , were compared. Pigment concentrations were determined at 485 nm, as described by Evans and Howells (38). …”
Section: Methodsmentioning
confidence: 99%